2015
DOI: 10.1371/journal.pone.0135178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Country of Birth on Type-1-Diabetes Therapy and Outcome in 27,643 Children and Adolescents from the DPV Registry

Abstract: ObjectiveTo study the impact of maternal country of birth on type-1-diabetes (T1D) therapy and outcome.Study Design and Methods27,643 T1D patients aged ≤20 years with documented maternal country of birth from the multicenter German/Austrian diabetes patient registry (DPV) were analyzed. Patients were categorized based on their mother’s origin: Germany/Austria (reference), Turkey, Southern Europe, and Eastern Europe. To compare BMI standard deviation score (BMI-SDS), diabetes therapy and outcome between groups,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 36 publications
2
29
0
3
Order By: Relevance
“…The trend towards a reduced rate of SH after publication of the results of the DCCT is in agreement with other recent convincing studies and reviews . For example, in the Epidemiology of Diabetes Interventions and Complications (EDIC) study—an approximately 30‐year follow‐up of DCCT patients—the incidence of SH decreased from 62.0 to 40.8 per 100 PY in the initial intensive therapy group .…”
Section: Discussionsupporting
confidence: 89%
“…The trend towards a reduced rate of SH after publication of the results of the DCCT is in agreement with other recent convincing studies and reviews . For example, in the Epidemiology of Diabetes Interventions and Complications (EDIC) study—an approximately 30‐year follow‐up of DCCT patients—the incidence of SH decreased from 62.0 to 40.8 per 100 PY in the initial intensive therapy group .…”
Section: Discussionsupporting
confidence: 89%
“…Ethnicity and migration background were associated with HbA1c level in Europe, America, and Israel . In the US, HbA1c level was found to be higher in T1D patients belonging to ethnic minority groups, with a mean HbA1c level difference varying between 0.9% (9.8 mmol/mol) and 1.5% (16.4 mmol/mol) in African‐Americans compared with Caucasian‐Americans .…”
Section: Resultsmentioning
confidence: 98%
“…The sample size range is 70 to 30 708 patients with a median sample size of 210 T1D patients. Thirty‐two studies were performed in several European countries, 31 in USA, one in Canada, three in Israel, and the rest in other countries (one in Japan, one in New‐Zealand, three in Turkey, one in Australia, and three are multinational). Most studies (54 studies) were performed on T1D children (median of mean age reported in articles 12.5 [range: 4.1‐17.7]), 22 included both children and young adults (median of mean age of 14.8 [range: 10.1‐21.6]), and one included only young adults (mean age of 19.4 ± 0.9 [range: 18‐21]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the urbanization movement in emerging countries, many children and their parents become dislocated as newcomers to cities, while leaving their home along with extended family members. Studies in different countries demonstrate that children with diabetes from new migrant families have poorer glycemic control, higher BMI, lower utilization of technologies and higher frequency of diabetes‐related hospitalization than the general endemic population suggesting that specific psychosocial, cultural, and biological challenges have to be considered in the clinical care of these families …”
Section: Care For Minority Children and Children Of Recent Immigrantsmentioning
confidence: 99%